Peran Human Capital Management dalam Meningkatkan Aktivitas Usaha Wizzmie di Kota Medan - Wintasya Manullang; Hawarul Ain Nisrina; Zaki Amirzah Saragih; Dionisius Sihombing; Fadly Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the role of Human Capital Management in enhancing the operational activities of the MSME Wizzmie in Medan, serving as an example of human resource management practices in small-scale enterprises. A descriptive qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and document analysis of HR practices within the MSME. The findings indicate that human resource strategies such as selective recruitment, routine training to improve employee competencies, structured task allocation, and performance-based reward systems significantly enhance employee discipline, skills, and service quality. Improvements in these areas contribute positively to smooth daily operations, customer satisfaction, and sales growth. Despite facing challenges, such as occasional lapses in employee discipline, management implements solutions including coaching programs, direct guidance, and a graduated warning system to address these issues. These results underscore that Human Capital Management is not merely an administrative function but plays a strategic role in fostering work efficiency, customer loyalty, and the sustainability of MSMEs. Consequently, effective human resource management emerges as a crucial factor for the success and competitiveness of small enterprises in a highly competitive business environment. The study highlights the importance of aligning HR practices with strategic business objectives to ensure long-term operational effectiveness and growth.